ANALISIS FAKTOR KEGAGALAN MEDIATOR DALAM MENDAMAIKAN PERKARA SENGKETA WARIS DI PENGADILAN AGAMA KABUPATEN KEDIRI (AL MUNAZHZHARAH, 2026)
In family life, when dividing inhertance, problems often arise and if the proble cannot be resolved because it is quite complicated, it is done in the religious court. And if the matter reaches the religious court then it must go through mediation so that the inheritance dispute does not drug on, wich is done by the mediator, often the mediator here fails to reconcile a case.The aim of this research is to analyze the process carried out bymediators in resolving dispute cases and analyze the factors of failure of mediators in the Kediri Regency Religius Court. The type of research carried out by the author is research using empirical legal researchmethods, where research is intended to use empirical facts by conducting interviews to obtain the required data. The approach to research uses a legal sociological approach that analyzes reactions and interactions when legal nomrs operate in society. There are two supporting data in the research which include primary research data and secondary research data with data collection and documentation techniques, then the data is analyzed using the stages of data reduction, data validation, data classification and data analysis. This research concludes that the mediation process in the Kediri Regency Religious Court is in accordance with Perma No. 1 of 2016. Starting from the pre-mediation process to the mediation results. Meanwhile, the factors that influence the failureof mediation at the Kediri Regency Religious Court consist of court factors, the lack of certified mediators. Furthermore, there are factors from the mediator, namely the lack of skills of the mediator in reconciling cases,communication that is less effective and the mediator's opinion is not listened to by the parties involved in the case and then there are factors from the parties where there is language that makes the defendant offended, andthere is a desire to power of the plaintiff to control the  inheritance.